2000
DOI: 10.1002/1097-0290(20001005)70:1<25::aid-bit4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cell culture factors can affect the glycosylation of Asn-184 in CHO-produced tissue-type plasminogen activator

Abstract: Human tissue-type plasminogen activator (t-PA) contains a variably occupied glycosylation site at Asn-184 in naturally produced t-PA and in t-PA produced in recombinant Chinese hamster ovary (CHO) cells. The presence of an oligosaccharide at this site has previously been shown to reduce specific activity and fibrin binding. In this report, the site occupancy of t-PA is shown to increase gradually over the course of batch and fedbatch CHO cultures. Additional cell culture factors, including butyrate and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 45 publications
(53 reference statements)
10
55
1
Order By: Relevance
“…This effect was also found in the production of human tissue-type plasminogen activator. A decline in growth rate induced by the supplementation of butyrate resulted in an enhanced glycosylation site occupancy (Andersen et al, 2000).…”
Section: Specific Cell Growth Rate and Protein Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was also found in the production of human tissue-type plasminogen activator. A decline in growth rate induced by the supplementation of butyrate resulted in an enhanced glycosylation site occupancy (Andersen et al, 2000).…”
Section: Specific Cell Growth Rate and Protein Productivitymentioning
confidence: 99%
“…Limitations in glucose and glutamine have been found to affect IFN-γ site-occupancy in CHO cultures (Hayter et al, 1992;Nyberg et al, 1999). In 2000, Andersen's group found that the site-occupancy of recombinant human t-PA was elevated gradually over the course of batch and fed-batch CHO cultures (Andersen et al, 2000). By controlling cell culture factors, including butyrate and temperature, they also showed the degree of site-occupancy that could be influenced (Andersen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of various cell culture factors, glycosylation variations in mammalian cell bioprocesses can found in the glycan site (macroheterogeneity) and glycan profile (microheterogeneity). 16 Glycan structures that are produced from any cell are governed by a network of enzymes that do not always allow for individual reactions. This network is affected by multiple factors, including the availability of precursor, co-factors and enzyme activities levels, all of which give rise to the variable final glycan structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that modification of the perfusion rate during a perfusion process, as well as modification of other bioprocess factors, can influence the recombinant protein quality and in particular its glycosylation pattern (Jenkins et al 1996;Andersen et al 2000). Glycosylation is usually recognized as an important function in the solubility, immunogenicity, and pharmacokinetic properties of human glycoproteins and those are the key parameters in the safety and clinical efficacy of a product (Goochee et al 1991).…”
Section: Introductionmentioning
confidence: 99%